Single step and dynamic balancing of YICAL Leg II using a position control algorithm - Abad, Eduard P.
Robots are used for various purposes such as prosthetics, entertainment, perform simple human tasks, and tasks that are too dangerous for humans to carry out. The legs are the foundation of a humanoid robot. The ability of a humanoid to walk and perform locomotive tasks is based on the leg's movement capability. The Yamatake Industrial Control and Automation Laboratory (YICAL) was able to produce a series of bipedal robots. The YICAL Leg II was made in 2006 to address the improvements and modifications from its predecessor, the YICAL Leg I. To implement dynamic walking to these bipedal robots, an attitude estimation system was developed to provide feedback for balancing algorithms. This project made the YICAL Leg II achieve a single step while being able to maintain its balance without any external support. The balancing algorithm was the stepping stone to implement dynamic walking on the bipedal robot. The position of each joint was solved using inverse kinematics. The TMS320F2812 Digital Signal Processor performed the necessary computations given the desired position and the compensation needed provided by the feedback system. The chip sent the corresponding signals to the motor driver to move each joint to its desired angle to make the biped perform a single step or to maintain balance.